Forensic Support for Investigating Criminal Offenses Committed against Law Enforcement Officers: Concept and Components - V. O. Husieva (Bulletin of Kharkiv National University of Internal Affairs)
The subject matter of the research is the features of forensic support for investigating criminal offenses committed against law enforcement officers. The purpose of the article was to define the concept, content, structure of forensic support for investigating criminal offenses committed against law enforcement officers, as well as to reveal its components.